Artificial Intelligence Enhancing Physical Education: A systematic literature review - Zhao, Juan; Sitthiworachart, Jirarat; Ratanaolarn, Thanin (My University, 2024)
This study aims to systematically review the application of Artificial intelligence (AI) technology to enhance physical education (PE). To this end, 104 journals in the databases of Baidu Scholar, Google Scholar, and King Mongkut's Institute of Technology Ladkrabang Library from 2014 to October 2023 were selected as research objects, and the research results were analyzed using the content analysis method. The analysis results show that the first research on this topic was conducted in 2014, and the Number of relevant studies has increased yearly, especially during the pandemic. In addition, these studies were mainly conducted in a combination of quantitative and qualitative, mainly journal articles. In addition, the samples of these studies are from each academic section, and most of the studies are conducted by college students. The analysis focuses on article distribution, publication time, research content, technology selection, and current and future challenges and summarizes the development trend, specific applications, benefits, and challenges of AI sports. The findings of the studies revealed that AI technology in PE can improve students' physical achievement, cognition, and learning habits. On the other hand, AI technology can enhance the effect of PE so that students have a greater interest in learning sports. Finally, some suggestions for future research are put forward.
Keywords: Artificial Intelligence; educational technology; physical education